Emergence of a service platform: The case of pet industry - Faghankhani, Hoda (My University, 2014)
Recent innovative ideas in the world of business have facilitated our everyday lives in a wide range of services and products, such as mobile, internet, credit card, media and even department stores. These innovations do not necessarily solely deal with technological advances, but also business model innovations. Platform business models have become so pervasive that without them our daily lives have encountered serious challenges. Such platforms intensively increase the efficiency of value creation and value capturing in comparison with their old-fashion product business counterparts. Currently, increasing number of industries attempt to substitute platforms with products and utilize this value creation approach with traditional approaches they already used to follow. However, researchers have paid less attention to the implications of establishing a new platform. Thus, this study aims to investigate the necessary steps required to establish a new platform in a market. This study investigates pet industry in Finland, which is not a mature market. The need to establish a platform has already been felt in this market. First, interviews are conducted with pet medical clinics to gather data about the market and current other incumbents of the market. Then, thematic coding has been used to analyze the obtained data. The results provided information about the themes identified through thematic coding, which generally confirmed our hypothesis about the need of establishing a platform in this market. We utilized the method which Casey, et al. (2010) used to study a similar case in Wireless local Area Access market. The results are used to identify which players should participate in value configuration networks and which role should be played by which participant. Finally, the study suggests and discusses possible value configuration networks in the pet health platform.
Keywords: platform business models; platform strategy; service platform